Informing Evidence Based Decisions: Usage Statistics for Online Journal Databases - Botchkarev, Alexei (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – The primary objective was to examine online journal database usage statistics for a provincial ministry of health in the context of evidence based decision-making. In addition, the study highlights implementation of the Journal Access Centre (JAC) that is housed and powered by the Ontario Ministry of Health and Long-Term Care (MOHLTC) to inform health systems policy-making.Methods – This was a prospective case study using descriptive analysis of the JAC usage statistics of journal articles from January 2009 to September 2013.Results – JAC enables ministry employees to access approximately 12,000 journals with full-text articles. JAC usage statistics for the 2011-2012 calendar years demonstrate a steady level of activity in terms of searches, with monthly averages of 5,129. In 2009-2013, a total of 4,759 journal titles were accessed including 1,675 journals with full-text. Usage statistics demonstrate that the actual consumption was over 12,790 full-text downloaded articles or approximately 2,700 articles annually.Conclusion – JAC’s steady level of activities, revealed by the study, reflects continuous demand for JAC services and products. It testifies that access to online journal databases has become part of routine government knowledge management processes. MOHLTC’s broad area of responsibilities with dynamically changing priorities translates into the diverse information needs of its employees and a large set of required journals. Usage statistics indicate that MOHLTC information needs cannot be mapped to a reasonably compact set of “core” journals with a subsequent subscription to those.